2016
DOI: 10.1098/rsif.2016.0070
|View full text |Cite|
|
Sign up to set email alerts
|

Estimating oxygen distribution from vasculature in three-dimensional tumour tissue

Abstract: Regions of tissue which are well oxygenated respond better to radiotherapy than hypoxic regions by up to a factor of three. If these volumes could be accurately estimated, then it might be possible to selectively boost dose to radio-resistant regions, a concept known as dose-painting. While imaging modalities such as 18F-fluoromisonidazole positron emission tomography (PET) allow identification of hypoxic regions, they are intrinsically limited by the physics of such systems to the millimetre domain, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 31 publications
3
62
0
Order By: Relevance
“…Complexity of experiments and lack of available resources are most likely the reasons for this. The method employed by Grimes et al [145] stains for hypoxic regions in tumour tissue; however, for healthy soft tissue this can pose a problem as no hypoxic regions should in theory be present. Instead, a tissue stain to mark oxygenation could be used, allowing validation of the results from computational modelling by use of gold standard light microscopy.…”
Section: Limitation 2: Validation Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complexity of experiments and lack of available resources are most likely the reasons for this. The method employed by Grimes et al [145] stains for hypoxic regions in tumour tissue; however, for healthy soft tissue this can pose a problem as no hypoxic regions should in theory be present. Instead, a tissue stain to mark oxygenation could be used, allowing validation of the results from computational modelling by use of gold standard light microscopy.…”
Section: Limitation 2: Validation Of Resultsmentioning
confidence: 99%
“…The only mathematical model presented in this section, validated against experimental data, is the rsif.royalsocietypublishing.org J. R. Soc. Interface 14: 20160992 tumour oxygenation model presented by Grimes et al [145]. Complexity of experiments and lack of available resources are most likely the reasons for this.…”
Section: Limitation 2: Validation Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small studies testing temporal stability of hypoxia in NSCLC have so far found inconclusive results. Some studies have observed stable hypoxia [39,40], whereas others have reported a decrease in hypoxia [26,41], or a mix of stable and dynamic hypoxia [42]. Lin et al [43] showed in head and neck cancer that when there is a spatial shift, dose painting of the initial subvolume still results in improved equivalent uniform dose on a later scan.…”
Section: Discussionmentioning
confidence: 99%
“…To acquire knowledge about vascular permeability, the DCE-CT scans should include images acquired around two to ten minutes after injection that will show this transition from the vascular to the extravascular space and back [38,39]. …”
Section: Dynamic Contrast-enhanced Ctmentioning
confidence: 99%